Practical guidelines for Argatroban and Bivalirudin in patients with Heparin-induced Thrombocytopenia. Issue 2 (2015) - Colucci, Giuseppe; Nagler, Michael; Klaus, Nicole; Conte, Tiziana; Giabbani, Evelyne; Alberio, Lorenzo
No abstract available